“Maximalism with an Experimental Twist”: Insider Trading Law at the Supreme Court - Zachary J. Gubler (Washington University Journal of Law & Policy, 2018)
This article, by Professor Zachary J. Gubler of Arizona State University’s Sandra Day O’Connor College of Law, examines the shape of the Supreme Court’s insider trading jurisprudence. Gubler argues that the Court ought to adopt an approach of “maximalism with an experimental twist” – a combination of broad-based opinions that go beyond the facts of a particular case, as well as a standards-based approach to assessing policy assumptions of the lower courts. Gubler uses this framework to evaluate the Court’s insider trading jurisprudence and argues that the Roberts Court missed an opportunity in Salman v. United States to offer meaningful clarification in insider trading law.
Keywords: deference; maximalism; institutional; expertise; legislature; agencies; Salman v. United States; experimentation; information sharing; SEC; minimalism; democratic; decision costs; error costs; liability; standards; rules; Chiarella; Dirks; clear; muddy; Salman